An oxorhenium complex bearing a chiral cyclohexane‐1‐olato‐2‐thiolato ligand: Synthesis, stereochemistry, and theoretical study of parity violation vibrational frequency shifts. Issue 2 (15th November 2017) - Saleh, Nidal; Bast, Radovan; Vanthuyne, Nicolas; Roussel, Christian; Saue, Trond; Darquié, Benoît; Crassous, Jeanne
Abstract: In our effort towards measuring the parity violation energy difference between two enantiomers, a simple chiral oxorhenium complex5 bearing enantiopure 2‐mercaptocyclohexan‐1‐ol has been prepared as a potential candidate species. Vibrational circular dichroism revealed a chiral environment surrounding the rhenium atom, even though the rhenium is not a stereogenic center itself, and enabled to assign the (1 S, 2 S )‐(−) and (1 R, 2 R )‐(+) absolute configuration for5 . For both compound5 and complex4, previously studied by us and bearing a propane‐2‐olato‐3‐thiolato ligand, relativistic calculations predict parity violating vibrational frequency differences of a few hundreds of millihertz, above the expected sensitivity attainable by a molecular beam Ramsey interferometer that we are constructing. Abstract :